Ethnography Research: Dayak Kaharingan Ethics Kalimantan - Daito, Apollo (Dinasti Research, 2023)
This research is an ethnographic on the Kaharingan Dayak in Central Kalimantan, East Barito, and South Kalimantan in Tabalong District, and Gunung Meratus Dayak. The studies were conducted in 2012, 2016, 2018 and 2023. The research units were the male and female Wadian Kaharingan, and the Mantir Adat Dayak. The results of this ethnographic research produced 3 main findings, namely the Dara Mula Lapeh Ethics of Concern, Datu Mula Munta's Environmental Ethics, and the third is the Ethics of Living Together on the Land. The Caring Ethics develops the notion of caring as a feminine ethic, and applies it to the practice of moral education. Women